Oviposition strategies of large cabbage moth (Crocidolomia pavonana) on Chinese cabbage - Sulifoa, J.B.; Furlong, M.J.; Kant, R. (New Zealand Plant Protection, 2016)
Crocidolomia pavonana F (Lepidoptera Crambidae) is an important pest of brassica crops in Samoa and in other countries in the South Pacific This study investigated the oviposition behaviour of C pavonana on Chinese cabbage in Samoa This research was carried out in field and laboratory experiments at the University of South Pacific Samoa The study showed that female C pavonana oviposited more days Linear regression analysis showed that egg mass size decreased as females aged Younger females (ca 2dayold) laid up to 141 eggs per egg mass whereas older females (ca 30daysold) laid up to 3 eggs per egg mass Females deposited >92 of their eggs on the lower surface of the leaf Most eggs were found near the midrib The eggs were also laid near the petiole (67) compared to the central or top (33) parts of the leaf Only a few eggs were oviposited on the petiole or the stem of the plant